Lack of Data and other Problems of Economic Policy Advice in Germany - Justus Haucap (Wirtschaftsdienst)
Abstract The relationship between politics and scientific policy advice is still characterized by misunderstandings on both sides. A major point of criticism from the political arena is repeatedly the lacking concern for reality in economics. This problem, however, is at least partly homemade, as the data situation is not good in many areas in Germany, even for research purposes. In addition to other reasons — such as incentives to publish in top international journals, which in turn seems to be easier with U.S. topics or data than with issues relevant to other countries — the lack of data availability also contributes to the fact that economists in the D/A/CH area deal less with “local” topics than would be possible.